Physiological characteristics of three cassava cultivars - Fahl, Joel Irineu; Machado, Eduardo Caruso; Pereira, Antonio Roberto; Arruda, Hermano Vaz; Lorenzi, José Osmar (Pesquisa Agropecuaria Brasileira, 2014)
Root production, harvest index, and leaf area index of three cassava cultivars (Manihot esculenta Crantz) Branca de Santa Catarina, IAC-12-829, and IAC-7-127- Iracema were not significantly affected by the planting densities (10,000, 16,666 and 25,000 plants/ha). The harvest index approached asymptotically the value 0.67. Cultivars with the heaviest stem had the lightest root. Maximum leaf area index achieved was 4.0 for all varieties. Cultivars IAC-12-829 and Branca de Santa Catarina had the highest root yield, while Branca de Santa Catarina had the highest plant weight. Maximum crop growth rate were, respectively, 11,5 g . m-2. day-1 , for Branca de Santa Catarina; 10,2 g . m-2 . day-1 for IAC-12-829; and 8.8 g . m-2 - day-1 for IAC-7-127- Iracema. Maximum root growth rate followed the same sequence with 6.9, 6.3, and 6.2 g m-2 . day-1, respectively. Accumulation of dry matter in the roots began only after the plants had approximately 270 g . m-2.